Stigma Diri dan Subjective Well-Being pada Remaja yang Melahirkan Di Usia Dini Di Kota Ambon - Christy Jacobs; Venti Agustina; Arwyn Weynand Nusawakan (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
ABSTRACT Self-stigma is the result of other people's judgments applied to oneself and it is possible to have an impact on the subjective well-being, which affects psychological and social conditions. Subjective well-being is a picture of life evaluation, emotional experience affective and cognitive. The purpose of this study is to describe the picture of self-stigma and subjective well-being of teenagers who giving birth at an early age in Ambon City. This study uses qualitative methods, with case study design and sampling techniques using purposive sampling. A total of eight teenagers who giving birth at an early age were participants. Data collection techniques using structured interviews, thematic analysis with data validity testing using source triangulation techniques. The results of self-stigma research in teenagers who giving birth at an early age, are considered not a good women, embarrassing parents and unable to look after themselves. While the subjective well-being felt by teenagers is related to positive affect which is gratitude and responsibility after becoming a mother, while negative affect is the needs of children can not be fulfilled and there are feelings of sadness, which causes teens not satisfied with their lives. The conclusion of this study shows, the picture of self-stigma and subjective well-being in teenagers who giving birth at an early age in Ambon City affects social relationships, changes in priorities and roles, so that these teens need support from the family. ABSTRAK Stigma diri ialah hasil dari penilaian orang lain yang diterapkan pada diri sendiri dan dimungkinkan berdampak pada subjective well-being, yang mepengaruhi kondisi psikologis dan sosial. Subjective well-being merupakan gambaran evaluasi kehidupan, pengalaman emosional secara afektif dan kognitif. Tujuan penelitian ini untuk mendeskripsikan gambaran stigma diri dan subjective well-being pada remaja yang melahirkan di usia dini di Kota Ambon. Penelitian ini menggunakan metode kualitatif, dengan desain studi kasus dan teknik pengambilan sampel menggunakan purposive sampling. Sebanyak delapan remaja yang melahirkan diusia dini menjadi partisipan. Teknik pengumpulan data menggunakan wawancara terstruktur, analisis tematik dengan uji keabsahan data menggunakan teknik triangulasi sumber. Hasil penelitian stigma diri pada remaja yang melahirkan di usia dini, cenderung dianggap bukan perempuan baik-baik, membuat malu orang tua dan tidak dapat menjaga diri. Sementara subjective well-being yang dirasakan oleh remaja terkait afek positif yakni ada rasa syukur dan ada tanggung jawab setelah menjadi seorang ibu, sedangkan afek negatif yaitu kebutuhan anak belum bisa terpenuhi dan ada perasaan sedih, yang menyebabkan remaja belum puas dengan hidupnya. Kesimpulan penelitian ini menunjukan, gambaran stigma diri dan subjective well-being pada remaja yang melahirkan di usia dini di Kota Ambon mempengaruhi hubungan sosial, perubahan prioritas dan peran, sehingga remaja tersebut membutuhkan dukungan dari keluarga.